Structure of human cystathionine β-synthase: a unique pyridoxal 5′-phosphate-dependent heme protein - Meier, Markus (Oxford University Press, 2001)
Cystathionine β-synthase (CBS) is a unique heme- containing enzyme that catalyzes a pyridoxal 5′-phosphate (PLP)-dependent condensation of serine and homocysteine to give cystathionine. Deficiency of CBS leads to homocystinuria, an inherited disease of sulfur metabolism characterized by increased levels of the toxic metabolite homocysteine. Here we present the X-ray crystal structure of a truncated form of the enzyme. CBS shares the same fold with O-acetylserine sulfhydrylase but it contains an additional N-terminal heme binding site. This heme binding motif together with a spatially adjacent oxidoreductase active site motif could explain the regulation of its enzyme activity by redox changes.